KEMAMPUAN MAHASISWA PPL MERUMUSKAN TUJUAN PEMBELAJARAN PADA MATERI SMA/MA KELAS X - Devita Sulistiana (Universitas Islam Balitar, 2016)
This study is aimed at seeing formulation of Specific Instructional Objectives (SIO) developed in the sciences materials by students conducting teaching practice at SMA. This study used descriptive design and assigned subjects of the whole students from Biology Department of UNISBA year 2012/2013. Data of the study included: (1) SIO and its characteristics of its elements: compehensiveness, appropriateness, specification, and attainment, (2) organization of the SIO referring to ABCD, audience, behavior, condition, degree. The study found that SIO that is appropriate to the criteria are: (1) appropriate to the good criteria 58.04% (good), (2) appropriate to the elements of SIO is 98.34%, and (3) appropriate structure regarding level II is 72.32% good, and 23.66% fair.